Prevalence of Depression in College Students During Covid-19 Pandemic - Samiksha Sathe1 , Kirti Thodge2 , Abhishek Joshi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The outbreak of Covid-19 has caused major amount of suffering around the globe. Along with the physicalsymptoms in affected cases, it has severely spoilt the mental health of general public. College students too arefacing multiple challenges in the stir of this COVID-19 outbreak. The present research is an attempt to assessthe prevalence of depression among students residing in Nagpur region. A total 433 students responded tothe online 9-item questionnaire (PHQ 9) based survey. Our survey showed that 96% of college students wereaffected with varied levels (minimal to severe) of depression resulting from the COVID-19 pandemic. ofthese, about 9% experienced severe depression, about 13% experienced moderately severe depression, about21% experienced moderate depression, about 29% experienced mild depression and about 23% experiencedminimal depression. It is suggested that a timely concern should be given to students’ psychological healthas they are flagbearers of country’s success and future.